The Influence of Discipline, Loyalty, and Work Motivation on Employee Performance in Financing Distribution at PT Permodalan Nasional Madani Pematang Siantar Branch Office - Pohan, Hendi; Marsono, Acong Dewantoro (Formosa Journal of Applied Sciences, 2024)
This study focuses on PT. Permodalan Nasional Madani (PNM) Pematang Siantar Branch, with independent variables of discipline, loyalty, and work motivation, and the dependent variable being employee performance. The primary aim is to evaluate the impact of these three independent variables on employee performance in the context of financing distribution. The sample consists of 100 PNM employees from the Pematang Siantar Branch, selected using a census method, with data analysis conducted through SEM using SmartPLS. This includes multiple linear regression, correlation, and determination coefficients. Data were collected through questionnaires distributed to all sample participants. The study results indicate that discipline does not influence employee performance. However, loyalty has a positive and significant effect on employee performance, as does work motivation.